An efficient manganese-oxidizing fungus Cladosporium halotolerans strain XM01: Mn(II) oxidization and Cd adsorption behavior. (January 2022) - Wang, Mei; Xu, Zuxin; Dong, Bin; Zeng, Yifan; Chen, Sisi; Zhang, Yunhui; Huang, Yangrui; Pei, Xiangjun
Abstract: The applications of biogenic Mn oxides (BMOs) formed by Mn-oxidizing fungus in decontaminating heavy metals have attracted increasing attention. In this study, an efficient Mn-oxidizing fungus was isolated from soil and identified as Cladosporium halotolerans strain XM01. The Mn(II) adsorption and oxidation activities of this strain were investigated, showing significantly high removal and oxidation rates of soluble Mn(II) of 99.9% and 88.2%, respectively. Dynamic analysis of the Mn(II) removal process demonstrated the oxidation process of Mn(II) to Mn(III) was the rate-limiting step in the Mn(II) metabolic process. The XRD and SAED characterization showed that more layers were orderly accumulated along the c -axis with the formation of fungal BMOs, which might lead to the decrease in its specific surface area. The adsorption of Cd(II) by the formed BMOs was investigated and compared with two typical abiotic Mn oxides, indicating that the adsorption capacity decreased with the following order: immature BMO, mature BMO, δ-MnO2, acid birnessite, while the fixation capacity decreased in the order of acid birnessite, mature BMO, δ-MnO2, immature BMO. The inverse correlation between the capacity of Cd(II) adsorption and fixation of immature and mature BMOs was probably attributed to the increase in the layer stacking of BMOs. This result indicates an interesting phenomenon of high reservation of Cd(II) resulting from sequential transformation from strong adsorption to strong fixation with the formation of BMOs. This study offers considerable insights into fungal Mn oxidation mechanisms and provides theoretical guidance for fungal BMOs in heavy metals bioremediation. Graphical abstract: Image 1 Highlights: An efficient Mn-oxidizing fungus of Cladosporium sp. XM01 was isolated. Strain XM01 had a strong ability for Mn(II) removal (99.9%) and oxidation (88.2%). More layers were orderly accumulated with the formation of BMOs. Cd(II) was preferentially adsorbed onto BMOs rather than abiotic Mn oxides. Immature BMO had the best adsorption capacity for Cd(II).